Historical periods and temporary discontinuities: an interpretation essay - Silva, Renán (2021)
Establishing a period, setting a date, or separating two moments of a process are believed to be common operations by which two events can be characterized as «before» and «after». These appear as «simple gestures» repeated by historians in each of their investigations. However, when analyzed carefully, this operation shows all its complexity, revealing its difficulty. This essay aims to draw attention on this issue.